The Effect of Discipline and Work Environment on Work Productivity - Paldiyasa, Rifky; Pauzy, Depy Muhamad; Asyiah, Ai Kusmiati (CV. Ulil Albab Corp, 2024)
This research aims to determine and analyze the influence of discipline and the work environment, both simultaneously and partially, on the work productivity of production employees at PT. Tjiwulan Putra Mandiri. The method used in this research is a survey. With a research sample of 152 production employees as respondents. The data used is primary and secondary data. The analytical tool used in this research is multiple linear regression using the SPSS version 25 support application. The test results show that simultaneously the variables used in the research, namely discipline and work environment, have a significant effect on the work productivity of production employees at PT. Tjiwulan Putra Mandiri. Likewise, partially there is a significant influence of discipline on the work productivity of production employees, and there is a significant influence of the work environment on the work productivity of employees at PT. Tjiwulan Putra Mandiri.